2015
DOI: 10.1371/journal.pone.0116369
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the SthK Carboxy-Terminal Region Reveals a Gating Mechanism for Cyclic Nucleotide-Modulated Ion Channels

Abstract: Cyclic nucleotide-sensitive ion channels are molecular pores that open in response to cAMP or cGMP, which are universal second messengers. Binding of a cyclic nucleotide to the carboxyterminal cyclic nucleotide binding domain (CNBD) of these channels is thought to cause a conformational change that promotes channel opening. The C-linker domain, which connects the channel pore to this CNBD, plays an important role in coupling ligand binding to channel opening. Current structural insight into this mechanism main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 33 publications
5
44
0
Order By: Relevance
“…Thus, our analysis suggests that the more potent facilitation by cAMP is due to stronger effects on the closed to open transitions as well as to its greater binding affinity and as compared with cGMP. A similar suggestion was made in a recent study on the SthK (Schmidpeter et al, 2018), a CNG channel from Spirochaeta thermophila that is structurally and evolutionarily related to the HCN channels (Brams et al, 2014;Kesters et al, 2015), which showed that cGMP binds with an affinity that is similar to cAMP but that it opens the channel less efficiently. Structures of the HCN2 channel show that cGMP binds in the syn configuration whereas cAMP binds in the anti configuration, and that each ligand makes unique interactions within the binding site (Zagotta et al, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…Thus, our analysis suggests that the more potent facilitation by cAMP is due to stronger effects on the closed to open transitions as well as to its greater binding affinity and as compared with cGMP. A similar suggestion was made in a recent study on the SthK (Schmidpeter et al, 2018), a CNG channel from Spirochaeta thermophila that is structurally and evolutionarily related to the HCN channels (Brams et al, 2014;Kesters et al, 2015), which showed that cGMP binds with an affinity that is similar to cAMP but that it opens the channel less efficiently. Structures of the HCN2 channel show that cGMP binds in the syn configuration whereas cAMP binds in the anti configuration, and that each ligand makes unique interactions within the binding site (Zagotta et al, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…Crystal structures of all CNG and HCN channel C-linker/CNBD fragments (13,14,23,27), as well as the recent cryoEM structures of TAX4, HCN1, and CaM-inhibited Eag1 (12,15,28), demonstrate a compact architecture of the CNBDs and CNBHDs whereby each protomer forms (weak) intersubunit contacts with neighboring subunits (Fig. 3 C and D).…”
Section: Identification and Characterization Of A Functional Prokaryomentioning
confidence: 84%
“…The intersubunit elbow-on-shoulder contacts form a ring directly beneath the TMDs, and this interaction has been proposed to be dynamic during the cyclic nucleotide-dependent gating of CNG and HCN channels (1). The C-linker of LliK has a different conformation and quaternary organization than that observed in the crystal structures of CNG and HCN carboxyl-terminal fragments (13,14,23), as well as the recent cryoEM structures of TAX4, HCN1, and CaM-inhibited Eag1 (12,15,28) (Fig. 3 G-J and Movies S1-S3).…”
Section: Identification and Characterization Of A Functional Prokaryomentioning
confidence: 86%
“…Because cyclic nucleotide regulation is potentiated when the AЈ helix is coordinating metal ions with the membrane, it is plausible that upon cyclic nucleotide binding, the AЈ helix moves toward the membrane, and this movement makes the channel more likely to open. In a recent crystal structure of a C-terminal fragment of a bacterial CNG channel, SthK, the AЈ helix is moved upward, toward the presumed location of the membrane, when bound to an agonist (cAMP) but not when bound to an antagonist (cGMP) (39).…”
Section: Discussionmentioning
confidence: 99%